2014
DOI: 10.1007/s00381-014-2459-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for focal cortical dysplasia in children using intraoperative mapping

Abstract: Tailored resection of FCD lesions for intractable epilepsy can be safely performed in children with a good seizure outcome and low complication rate. Epilepsy surgery should be considered for all patients with FCD and refractory epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
7
1
Order By: Relevance
“…The proportion of patients achieving a favorable outcome in our meta-analysis is higher than in surgical series of histopathologically confirmed FCD that included MRI-positive and MRI-negative patients. 8,9,28-31 A previous meta-analysis of 37 such studies found that 55.8 ± 16.2% of patients with histopathologically confirmed FCD achieved Engel class I outcome at last follow-up. 11 These data reinforce the importance of identifying lesions suggestive of FCD on MRI because they can guide more effective surgical resections.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients achieving a favorable outcome in our meta-analysis is higher than in surgical series of histopathologically confirmed FCD that included MRI-positive and MRI-negative patients. 8,9,28-31 A previous meta-analysis of 37 such studies found that 55.8 ± 16.2% of patients with histopathologically confirmed FCD achieved Engel class I outcome at last follow-up. 11 These data reinforce the importance of identifying lesions suggestive of FCD on MRI because they can guide more effective surgical resections.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of improved and optimized solutions to the IUS images acquired during surgery. It is our opinion that the integrated 2D IUS and ultrasound installed BL systems using preoperative MRI gives better appreciation of the lesion dimensions in the axial, coronal and sagittal planes 3D views, which can improve the extent of resection Additionally, the use of ultrasound navigation software with BL systems integration enables the scanning and reconstruction of 3D ultrasound data noticeably faster than with intraoperative MRI, and this allows that the surgery is quicker and more efficient; this means that the surgical workflow is practically uninterrupted [14,15]. In a study carried out at their institution, Sacino et al investigated the use of intraoperative MRI and found that it increased the length of the procedure by 1.5 to 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a “critical pattern” of discharges lasting ≥2 s highly significant . In smaller series, other authors have used a semiquantitative scale in patients with either FCD or glioneuronal tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a "critical pattern" of discharges lasting ≥2 s highly significant. 25 In smaller series, other authors have used a semiquantitative scale in patients with either FCD or glioneuronal tumors. 8,26 In their assessments, discharges were categorized as sporadic, bursts, continuous, or recruiting.…”
Section: Clinical Implications Of Ecog Abnormalitiesmentioning
confidence: 99%